2008
DOI: 10.1111/j.1445-5994.2007.01519.x
|View full text |Cite
|
Sign up to set email alerts
|

Nurse‐led 24‐h hotline for patients with chronic obstructive pulmonary disease reduces hospital use and is safe

Abstract: A nurse-led 24-h hotline for patients with COPD is safe, is used by patients and carers and, when used, reduces hospital presentations with AECOPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
18
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 28 publications
4
18
0
Order By: Relevance
“…However, during the course of our service, a group from Australia have reported their findings. 16 44% of calls were received in office hours (here defined as Monday-Friday 0900-1700) and 25% of calls were not related to COPD. In contrast to our study, only one quarter of patients used the service.…”
mentioning
confidence: 99%
“…However, during the course of our service, a group from Australia have reported their findings. 16 44% of calls were received in office hours (here defined as Monday-Friday 0900-1700) and 25% of calls were not related to COPD. In contrast to our study, only one quarter of patients used the service.…”
mentioning
confidence: 99%
“…Those that have been published show significant demand for telephone support from service providers in the setting of a paediatric neurology service [7] and from parents of children with congenital anomalies following discharge from hospital [9]. There is more data in adult chronic disease populations where a significant demand for telephone support has been shown [10-12]. Providing telephone support is becoming an integral part of adult rheumatology care in England and Wales [13].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a nurse-led 24-hour hotline for patients with COPD is safe, is used by patients and caregivers, and potentially reduces hospital presentations even in a group of patients with severe disease (Roberts, Leeder, & Robinson, 2008). Nonspecifi c home-based intervention provides long-term cost benefi ts in a range of chronic illnesses, except for COPD.…”
Section: Discussionmentioning
confidence: 99%